PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS INFORMASI TANGGAL KADALUWARSA PRODUK MAKANAN BERDASARKAN UNDANG-UNDANG NO. 8 TAHUN 1999 (Studi Putusan NO.149/Pid.Sus/2017/PN.Ktb) - Leviana Rachel; Amad Sudiro (Fakultas Hukum Universitas Tarumanagara, 2020)
Legal protection for consumers on information on the expiration date of food products, especially food products sold by minimarkets. Sun. Often overlooked. In the field, the Minimarket Mentari sells food products that have no expiration date information, and it is even found that some packaged and canned foods do not include the expiration date so that it is very detrimental to food consumers and violates consumer rights. Kotabaru District Court Decision No. 149 / Pid.Sus / 2017 / PN.Ktb regarding the right to see consumers is not in line with Law no. 8 of 1999 concerning consumer protection. The ruling provides consumers with improper food legal protection. This research was conducted using normative legal research methods. Legal materials obtained by statute law and case law for normative analysis. Based on the results of the analysis, Law Number 8 of 1999 concerning Consumer Protection provides legal protection to consumers when food is damaged, it expires, in addition to their rights, they can also demand compensation, compensation or replacement of components in Article 4h. Get some good publicity through courts and BPSK as an effort to properly resolve disputes as stated in Article 4 letter e of the UUPK.